New fixed point results in b-rectangular metric spaces - Roshan, Jamal Rezaei Rezaei; Parvaneh, Vahid; Kadelburg, Zoran (Nonlinear Analysis: Modelling and Control, 2016)
In this work, the class of b-rectangular metric spaces is introduced, some fixed point results dealing with rational type contractions and almost generalized weakly contractive mappings are obtained. Certain examples are given to support the results.